1996
DOI: 10.1002/jbmr.5650110718
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor alleles, bone mineral density and turnover in premenopausal Japanese women

Abstract: Recent studies have shown that genetic effects on bone mineral density (BMD) and bone turnover are related to allelic variation in the vitamin D receptor (VDR) gene. We examined allelic influences of the VDR gene on bone turnover and density in 202 normal healthy premenopausal Japanese women (age 30.1 +/- 1.2, mean +/- SEM). The VDR effect on BMD and turnover is similar to that observed in Caucasian women; however, there are major differences in allele frequency. The B allele by BsmI restriction fragment lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Many previous studies on the effect of VDR gene polymorphism on renal diseases showed conflicting results. 9,11,12 No effects of the different VDR polymorphic genotypes on both chronic kidney disease and end-stage renal disease were previously documented, [20][21][22][23][24][25] whereas studies on systemic lupus erythematosus nephritis, including secondary nephrotic syndrome with or without renal dysfunction, reported an association of renal involvement with the bb genotype of BsmI polymorphism, which is a common single-nucleotide polymorphism of the VDR gene. 19 INS has been widely considered to be a primary immune disease associated with immune regulatory imbalance between Th1 and Th2 cytokines, which are thought to play major roles in the pathogenesis and progression of the disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies on the effect of VDR gene polymorphism on renal diseases showed conflicting results. 9,11,12 No effects of the different VDR polymorphic genotypes on both chronic kidney disease and end-stage renal disease were previously documented, [20][21][22][23][24][25] whereas studies on systemic lupus erythematosus nephritis, including secondary nephrotic syndrome with or without renal dysfunction, reported an association of renal involvement with the bb genotype of BsmI polymorphism, which is a common single-nucleotide polymorphism of the VDR gene. 19 INS has been widely considered to be a primary immune disease associated with immune regulatory imbalance between Th1 and Th2 cytokines, which are thought to play major roles in the pathogenesis and progression of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…10 Ethnic and genetic differences in the frequencies of the VDR polymorphic genotypes have been previously reported in different populations. 9,11,12 In this study, we explore the frequency of VDR gene TaqI and ApaI restriction fragment length polymorphisms (RFLPs) in Kuwaiti Arab children with INS and the effect of the different VDR polymorphic genotypes on steroid responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype was determined from the lengths of fragments, i.e. BB, Bb, and bb (PCR-restriction-fragmentsof-length-polymorphism method) [22].…”
Section: Analysis Of Vdr-bsmi Polymorphismmentioning
confidence: 99%
“…4 Several single nucleotide polymorphisms (SNPs) have been shown to influence BMD in adults, especially those of the vitamin-D receptor gene (VDR). [7][8][9][10][11][12] The extent of the influence of VDR SNPs on BMD may be dependent on age and menopausal state. 13 In healthy children, only a few studies on the influence of VDR 3'-end SNPs (BsmI, ApaI, TaqI) on BMD have been reported, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%